METHODS AND PROBLEMS OF GENETIC TOXICOLOGY (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
A brief review of in vitro and in vivo mutagenicity testing strategy and analysis of genotoxicity of new potential anticancer preparations (porphyrins derivatives) and anticancer preparation cisplatin with the comet assay, Comet-FISH and micronuclei test is presented. The directions presented are highly important for development of genetic toxicology in Armenia.
Keywords: genotoxicity; Comet-FISH; micronuclei test; mutagenicity testing strategy